Adjustment of Parental Involvement Behaviors to Avoid Social withdrawal - Hu, Haotian (Transactions on Social Science, Education and Humanities Research, 2024)
The purpose of this research is to delve into the connection between teenager social withdrawal (TSW) and parental involvement behavior (PIB) in China. Both TSW and PIB have four dimensions each; this study was motivated as social withdrawal surfaces as a growing issue in a society that is fast-paced with educational and economic development. Our analysis was based on questionnaire data, using measurement scales derived from existing literature. The study unearthed a negative correlation between overall levels of TSW and PIB, implying that higher levels of PIB are indicative of lower TSW. Further scrutiny showed that three dimensions of PIB significantly predicted lower TSW while ’life care’ did not play a role. Moreover, each dimension of PIB demonstrated negative correlations with one to two specific dimensions of TSW. This work can thus help parents gain an understanding on how their efforts towards parental involvement need adjustment so as to prevent higher levels of teenager social withdrawal.